The Atmosphere : An Introduction to Meteorology - Lutgens, Frederick K. ; Tarbuck, Edward J. and Tasa, Dennis (India Pearson, 2015)
Featuring examples of contemporary environmental issues, such as ozone depletion, global warming, acid rain, and air pollution.
Include Illustration, Graph, Table, Map, Glossary, Appendix and Index
Keywords: Meteorology -- Atmosphere -- Weather